2013
DOI: 10.1080/09613218.2013.808864
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impacts of summertime overheating: some adaptation strategies

Abstract: The UK is predicted to experience warmer summers in the future, but the domestic building stock in England was not designed to cope with this change. The Standard Assessment Procedure (SAP) 2009 is used to assess the current state of the English building stock in terms of its vulnerability to overheating. The English Housing Survey 2009 provided data for 16 150 dwellings which are weighted to represent the housing stock. SAP predicts 82% of dwellings are currently at 'slight' risk of overheating and 41% at med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
0
22
1
Order By: Relevance
“…For instance, Orme, Palmer and Irving [7] concluded that night time purging was the most effective single intervention to reduce overheating. Tillson et al [8] showed that using a combination of window shutters or overhangs and ventilation can greatly reduce overheating. Mavrogianni et al [9] investigated the effectiveness of thermal mass and insulation in reducing overheating.…”
Section: The Passivhaus Standard and Literature Reviewmentioning
confidence: 99%
“…For instance, Orme, Palmer and Irving [7] concluded that night time purging was the most effective single intervention to reduce overheating. Tillson et al [8] showed that using a combination of window shutters or overhangs and ventilation can greatly reduce overheating. Mavrogianni et al [9] investigated the effectiveness of thermal mass and insulation in reducing overheating.…”
Section: The Passivhaus Standard and Literature Reviewmentioning
confidence: 99%
“…A plethora of studies have used dynamic thermal simulation in order to see how different energy refurbishments might affect building overheating in current and future weather scenarios (Mavrogianni et al, 2012;Tillson et al, 2013;Porritt et al, 2011;Porritt et al, 2012;McLeod et al, 2013;Oikonomou et al, 2012;Ji et al, 2014;Barbosa et al, 2015). However, most of these studies use simple statements of ventilation patterns, for example, ventilation commencing when the room operative temperature reaches an assumed threshold temperature (Mavrogianni et al, 2012;Tillson et al, 2013;Porritt et al, 2011;Porritt et al, 2012). This is not representative of how windows are used in reality by occupants in homes, since it is based on studies in offices.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to uptake have led to an energy efficiency gap [87], which policy has not adequately addressed [88]. In addition to this range of non-cost factors, modelling needs to account for a range of other factors, such as rebound effects [89], the specificity of measures to building type, the degree of interaction with other aspects of the heating system, linkages with preventing winter mortality [90] and energy poverty [91], other risks such as over-heating [92,93], and broader supply chain issues relating to scaling up the deployment of energy efficiency measures. Appendix A.1.…”
Section: Discussionmentioning
confidence: 99%